ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH - Purba, Rahima Br.; Umar, Haryono; Nasution, Anggi Pratama; SM, Nia Amelija (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
Regional autonomy can provide an action for local governments where the action is both an opportunity and a challenge. Opportunities can be interpreted for local governments that have high natural resource potential that is adequate to be managed by themselves, while for local governments that have low natural resource potential is a challenge. As a result, the problem that always arises with regional governments in implementing regional autonomy is the ability to finance in order to carry out its function as a development organizer. The purpose of this study was to determine the financial performance of the North Sumatra Provincial Government from 2015 to 2019 and the level of stability in managing its resources. The data used in this study are the financial statements of the North Sumatra Provincial Government from 2015 to 2019. Data will be analyzed using four financial ratios, namely: A. Liquidity Ratio, B. Regional Financial Independence Ratio, C. Working Capital, D. Surplus / Deficit. The results of data analysis states that the financial performance of the North Sumatra Provincial Government when viewed from: A. Liquidity ratios are very large for the three fiscal years of 1.09: 1 (2015), 2.19: 1 (2016), 2.77: 1 (2017), but instability occurs in the 2 fiscal years amounting to 1.54: 1 (2018), 4.02: 1 (2019). B. Ratio of Regional Financial Independence for the Government of North Sumatra Province is still very low, the value of the independence ratio for 5 fiscal years is 1.4% (2015), 1% (2016), 0.65% (2017), 0.71 (2018 ), 0.70 (2019). C. Working Capital at the Provincial Government of North Sumatra also experienced instability caused by a decrease or increase in the value of working capital each period of IDR 14,828,365,948,405 (2015), IDR 115,459,656,851,686 (2016), IDR 172,682,206,980. 180 (2017), IDR 87,020,818,170,342 (2018), IDR 145,223,588,917,934 (2019). D. Surplus / deficit analysis results in the five fiscal years of the North Sumatra Provincial Government shows that the 2 fiscal years there was a deficit. The value of the surplus / deficit is IDR 375,203,376,142,209 (2015), IDR 964,195,015,857 (2016), (IDR 284,030,223,626) (2017), IDR 139,671,038,225 (2018), (IDR 360,844,313,448) (2019).